PENGARUH E-WOM FACEBOOK TERHADAP MINAT BELI MAHASISWA PEREMPUAN BERBELANJA ONLINE (STUDI PADA FAKULTAS EKONOMI USI PEMATANGSIANTAR, SUMATERA UTARA, INDONESIA) - Liharman Saragih (Jurakunman (Jurnal Akuntansi dan Manajemen), 2020)
Abstract This study aims to determine how the influence of E-WOM Facebook on the purchase intention of female students of Fakultas Ekonomi USI on shopping online. The results showed that online review had an effect of 76.1%. according to independent variables are seen the variable "Messenger" Factor and Qualitative Message Characteristics, are significant and positive influences while the Quantitative Message Characteristics variable on Facebook is not significant but positive on on the purchase intention of female students of Fakultas Ekonomi USI Pematangsiantar, Sumatera Utara, Indonesia on shopping online . It shown by test using spss 24 and the result is Y= 11,557 +0,274X1 +0,098X2+0,880X3+ e. Keywords :E-WOM, Messenge, Qualitative Message, Quantitative Message, purchase intention